BASKETBALL SHOOTING LEARNING MODEL FOR ELEMENTARY SCHOOL AGE 9-12 YEARS OLD - Zendy Praja; Ramdan Pelana; Widiastuti (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
This study aims to develop a basketball shooting learning model for elementary school (SD) children aged 9-12 years, in order to produce an efficient and effective basketball shooting learning model for improving basketball shooting for elementary school (SD) children aged 9-12 years old. This research is a development research using Research and Development from Borg and Gall. To determine the effectiveness of the product, an implementation process was carried out using a pre-experimental research design in the form of